Single-cell transcriptomic analysis of bloodstream Trypanosoma brucei reconstructs cell cycle progression and developmental quorum sensing - Emma M. Briggs (Nature Portfolio, 2021)
Trypanosoma brucei undergoes developmental steps during host infection. Here, using oligopeptide-induced differentiation in vitro, authors model replicative ‘slender’ to transmissible ‘stumpy’ bloodstream forms and identify developmental and cell cycle regulators by single cell transcriptomics.